White Light Electroluminescence by Organic-Inorganic Heterostructures with CdSe Quantum Dots as Red Light Emitters. (8th September 2011) - Oner, Ilker; Stathatos, Elias; Varlikli, Canan
Abstract : We have developed a white organic light-emitting diode featuring a double emission layer comprising a blue light-emitting conductive polymer as a host material for Cadmium Selenide (CdSe) quantum dots as red light emitters and tris-(8-hydroxyquinoline) aluminium thin layer for green light emission. The Commission Internationale de l'Eclairage coordinates of the emitting light of the device were found to be (0.32, 0.40) which were only slightly changed over a range of applied voltages between 5 and 10 volts. The use of CdSe nanocrystalline quantum dots (surface-stabilized with hexadecylamine/trioctylphosphine oxide ligands) in the hybrid heterostructure with poly(9, 9-di-n-octylfluorenyl-2, 7-diyl) conductive polymer was studied for a variety of CdSe concentrations developing the performance of the device in means of overcoming segregation problems in the blend. Besides, constituents' ratio was further examined for the exploration of possible energy transfer from polymer host material to the CdSe quantum dots as a key factor for well-balanced emission in the electroluminescent devices.